'Orwellian' Discourse in ELT: a Threat to Professional Diversity. (April 2015) - Waters, Alan
The diversity of opinion about pedagogy within ELT (English Language Teaching) makes it essential that its professional discourse is sufficiently inclusive. However, this often fails to occur because ELT professional discussion is frequently too 'Orwellian' in nature, i.e. behaves in a manner resembling the political structures in the novel 'Nineteen Eighty-Four' (Orwell, 1949). For example, a form of professional 'newspeak' often exists, whereby meanings of words are aligned with 'approved' ways of thinking, such as in the use of the term 'authentic'. A second frequent occurrence is 'thoughtcrime' (views contrary to those of the 'ruling party' being seen as unacceptable). The over-promotion of task-based learning can be seen as often taking such a form. Third, 'doublethink' (simultaneously believing in two contradictory ideas) is all too common, as in the advocacy of professional inclusivity, on the one hand, and the rejection of 'English as a Native Language' (ENL) as a pedagogical model on the other. As a result of such forms of 'thought control', a number of valid professional pedagogical perspectives are denigrated. The paper concludes by discussing how a less Orwellian and more representative form of professional discourse might be created.